To rewrite the function \( f(x) = x^2 + 4x + 3 \) in vertex form, we can complete the square.
Starting with: \[ f(x) = x^2 + 4x + 3 \]
We can complete the square:
-
Take half of the coefficient of \( x \) (which is 4), square it: \[ \left(\frac{4}{2}\right)^2 = 4 \]
-
Rewrite the function: \[ f(x) = (x^2 + 4x + 4) - 4 + 3 \ = (x + 2)^2 - 1 \]
Now we have expressed the function in vertex form: \[ f(x) = (x + 2)^2 - 1 \]
Here, the vertex of the parabola is given by the coordinates \( (-2, -1) \).
Therefore, we can fill in the blanks:
- Blank space 1: \((x + 2)^2 - 1\)
- Blank space 2: \(-2\)
- Blank space 3: \(-1\)
Complete Sentence:
Writing \( f(x) \) in the equivalent form \((x + 2)^2 - 1\) reveals the vertex of the parabola, which has the coordinates \((-2, -1)\).